Short-term 2.1 GHz radiofrequency radiation treatment induces significant changes on the auditory evoked potentials in adult rats. (2nd September 2018) - Hidisoglu, Enis; Kantar-Gok, Deniz; Ozen, Sukru; Yargicoglu, Piraye
Abstract: Purpose: There is a growing interest in the usage of radiofrequency radiation (RF) as a noninvasive brain stimulation method. Previously reported data demonstrated that RF exposure caused a change in brain oscillations. Therefore, we aimed to investigate effects of RF on brain oscillation by measuring the auditory response of different brain regions in rats. Materials and methods: Rats were randomly divided into three groups ( n  = 12 per each group): Cage control (C), sham rats (Sh), and rats exposed to 2.1 GHz RF for 2 h/day for 7 days. At the end of the exposure, auditory evoked potentials (AEPs) were recorded at different locations in rats. Latencies and amplitudes of AEPs, evoked power, inter-trial phase synchronization, and auditory evoked gamma responses were obtained in response to an auditory stimulus. Furthermore, TBARS levels and 4-HNE, GFAP, iNOS, and nNOS expressions were evaluated in all groups. Results: Peak-to-peak amplitudes of AEPs were significantly higher in the RF group compared with the Sh group. There is no significant difference in peak latencies of AEPs between groups. Beside, evoked power, inter-trial phase synchronization, and auditory evoked gamma responses were significantly higher in the RF group compared with the Sh group. In addition, the RF group had significantly lower TBARS and 4-HNE levels than the Sh group. There were no significant differences between groups for GFAP, nNOS, and iNOS levels, and between the C and RF groups for all parameters. Conclusions: Our present findings suggest that short-term RF treatment under chosen experimental conditions have statistically significant effect on neuronal networks of rats by probably reducing oxidative damage. However, this effect must be further studied for possible noninvasive brain stimulation.